Relações alométricas em Leucaena leucocephala (Lam.) De Wit - Aleixo, Valdemir (2006)
Concern with increase carbon dioxide emissions has fostered several studies throughout scientific knowledge. The greenhouse effect is recognized as necessary for Earth surface colonization. However, modern day carbon dioxide and other greenhouse effect gases are blamed for atmosphere warming and its catastrophic effects. Both the Kyoto treat and the policy of Mechanism of Clean Development have instigated new approaches to reward actions that result in carbon sequestration. The objective of this study was to calculate simple allometric equations in order to estimate above and below ground dry biomass from Leucaena leucocephala individuals of various sizes from the Marechal Candido Rondon county. The results indicated that the decreasing order of leucaena biomass are stem > branches > roots > leaves. Independently of individual size, 24 % of total dry biomass sampled in this study was located below ground and 76 % above ground. Log transformed linear equations using CBH (circumference at breast height) as independent variable was statistically significant (P<0.05) to estimate leucaena total dry biomass